Um estudo de caso da assessoria de comunicação de uma prefeitura municipal utilizando rede social como ferramenta de comunicação 4.0 - Sousa Junior, Júlio César de (Brasil, 2024)
In this study, the impact of 4.0 communication tools on a government public institution was explored, aiming to understand how these innovative technologies can enhance the delivery of information and services to citizens. The research focuses on identifying the main 4.0 communication tools, analyzing the benefits that social networks as a tool offer, and investigating the challenges faced in implementing these technologies. The literature review highlights the growing importance of Industry 4.0 and its associated technologies. Additionally, digital age communication tools such as social networks, blogs, messaging apps, podcasts, videos, and online collaboration platforms are discussed, along with how they are being utilized by governmental institutions. The results demonstrate that 4.0 communication tools offer significant opportunities to improve the provision of public services by governmental institutions.